Makna Kata dan Makna Istilah pada Lagu Sal Priadi "Gala Bunga Matahari" sebagai Implikasi Alternatif Pembelajaran Bahasa dan Sastra Indonesia - Annisa Putri Ramadhani; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Sal Priadi is a Male Songwriter and Singer. His song entitled Gala Sunflower is very popular among teenagers, especially today. This research was motivated by the desire to know the meaning of the words and terms in the song, which could become material for thought and reflection about life. The song Gala Sunflower tells of longing for someone who has died, and this research aims to understand the meaning of the words and terms contained in the song. Research on the song Gala Bunga Matahari to identify several things contained in the song, such as the various settings contained in the song, the meaning of words, the meaning of terms, and implement it as language and literature learning material. The research method used is a qualitative method from song sources using the note-taking technique. The steps used in understanding the song Gala Bunga Sunflower use hermeneutic techniques. Understanding the song Gala Bunga Sunflower can be linked to basic learning competencies, such as identifying the meaning of words and the meaning of terms. It is hoped that students can apply the meaning contained in Sal Priadi's song "Gala Bunga Matahari".